Activity- and sleep-dependent regulation of tonic inhibition by Shisa7 - Kunwei Wu (Cell Reports, 2021)
Summary: Tonic inhibition mediated by extrasynaptic γ-aminobutyric acid type A receptors (GABAARs) critically regulates neuronal excitability and brain function. However, the mechanisms regulating tonic inhibition remain poorly understood. Here, we report that Shisa7 is critical for tonic inhibition regulation in hippocampal neurons. In juvenile Shisa7 knockout (KO) mice, α5-GABAAR-mediated tonic currents are significantly reduced. Mechanistically, Shisa7 is crucial for α5-GABAAR exocytosis. Additionally, Shisa7 regulation of tonic inhibition requires protein kinase A (PKA) that phosphorylates Shisa7 serine 405 (S405). Importantly, tonic inhibition undergoes activity-dependent regulation, and Shisa7 is required for homeostatic potentiation of tonic inhibition. Interestingly, in young adult Shisa7 KOs, basal tonic inhibition in hippocampal neurons is unaltered, largely due to the diminished α5-GABAAR component of tonic inhibition. However, at this stage, tonic inhibition oscillates during the daily sleep/wake cycle, a process requiring Shisa7. Together, these data demonstrate that intricate signaling mechanisms regulate tonic inhibition at different developmental stages and reveal a molecular link between sleep and tonic inhibition.